Factors associated with depressive symptoms among cancer patients: a nationwide cross-sectional study - Xiaoqing Chen; Chaoyan Ye; Li Liu; Xiuyang Li (BMC, 2024)
Abstract Objective Research on factors contributing to depressive symptoms in cancer patients at a national level, encompassing a comprehensive set of variables was limited. This study aimed to address this gap by identifying the factors associated with depressive symptoms among cancer patients through a nationwide cross-sectional analysis. Methods Various factors, including demographic, socioeconomic, behavioral patterns, general and self-rated health status, chronic conditions, dietary habits, and cancer-related factors, were examined. Data was from the National Health and Nutrition Examination Survey. Univariate and multivariate logistic regression analyses were performed to identify associated factors. The receiver-operating characteristic (ROC) curve was used to evaluate the performance of the logistic model. Results The findings showed that five sociodemographic factors, two behavioral styles, self-rated health status, comorbid arthritis, two dietary factors and two cancer-related factors were strongly associated with depressive symptoms. Compared with those aged 20-39 years, cancer individuals aged 40-59 years (OR = 0.48, P < 0.05) and those 60 years or older (OR = 0.18, P < 0.05) had lower odds of depression. Positive factors included being never married (OR = 1.98, P < 0.05), widowed, divorced or separated (OR = 1.75, P < 0.05), unemployment (OR = 1.87, P < 0.05), current smoking (OR = 1.84, P < 0.05), inadequate sleep (OR = 1.96, P < 0.05), comorbid arthritis (OR = 1.79, P < 0.05), and poor self-rated health status (OR = 3.53, P < 0.05). No significant association was identified between the Healthy Eating Index 2015 and the Dietary Inflammatory Index with depression (P > 0.05). Shorter cancer diagnosis duration was associated with reduced odds of depression (P < 0.05). The logistic model had an area under the curve of 0.870 (95% CI: 0.846-0.894, P < 0.05). Conclusions Cancer patients should receive enhanced family and social support while cultivating a healthy lifestyle and diet. Incorporating plenty of fruits, greens, and beans is highly recommended, along with establishing a comprehensive health management framework.